Telomere length was associated with grade and pathological features of meningioma - Yamakawa, Keiko; Mukai, Yuri; Ye, Juanjuan; Muto-Ishizuka, Mariko; Ito, Masumi; Tanimoto, Misa; Suizu, Futoshi; Asano, Kenichiro; Kurose, Akira; Matsuda, Yoko (Scientific reports, 2022)
Telomeres are tandem repeats of the TTAGGG sequence at chromosomal ends and afford protection against chromosomal instability. To investigate the contribution of telomere dysfunction in meningiomas, here we estimate the associations between telomere length, tumor grade, and proliferation index in a series of 14 archived samples, using quantitative-fluorescence in situ hybridization, Ki67 immunostaining, and pathological analysis. The number of mitoses per 10 high-power fields (HPF) and Ki67 index was higher in grade III cases than in grade I or grade II cases. Telomere length was negatively associated with both the number of mitoses/10HPF and Ki67 index. Meningioma cases with atypical mitosis, a morphological marker of chromosomal instability, exhibited shortened telomeres. Among telomere-shortened meningioma cases, 40% were grade I, 20% were grade II, and 100% were grade III. In grade I or II meningiomas, shortened telomeres lacked high proliferation activity and atypical mitosis. In conclusion, telomere shortening might be pivotal in the development of high-grade meningioma. Analysis of telomere length might be a selective marker for meningiomas with high-grade malignant potential.